Patient‐reported outcomes in Friedreich's ataxia after withdrawal from idebenone. (8th April 2019) - Cook, Arron; Boesch, Sylvia; Heck, Suzette; Brunt, Ewout; Klockgether, Thomas; Schöls, Ludger; Schulz, Angela; Giunti, Paola
Abstract : Objectives: Friedreich's ataxia is the most common inherited ataxia, and pathogenesis is known to involve mitochondrial oxidative stress. Idebenone is a potent antioxidant which has already been evaluated in several clinical trials in FRDA, with reports of symptomatic benefit but inconclusive objective results. Following patient consultation on design, we have completed a treatment‐withdrawal study to establish whether patients could correctly determine their treatment allocation to placebo or idebenone. Our aim was to capture subjective experiences of symptoms such as fatigue, which can be difficult to measure with questionnaires or semi‐quantitative scales, particularly in chronic, slowly progressive conditions. Materials and Methods: Patients taking idebenone for at least 12 months as part of the open‐label MICONOS Extension Study were randomized to receive either placebo or idebenone continuation for 2‐month treatment cycles. The primary endpoint was patient assessment of treatment assignment. Results: A total of 29 patients were randomized, forming the idebenone group (n = 16) and the placebo group (n = 13). No significant differences were detected between the idebenone and placebo groups on assessment of treatment assignment or early study withdrawal. A small but significant difference in ataxia rating scale scores was detected between treatment groups when considering ambulatory patients only. Conclusions: This study provides no data to suggest that FRDA patients could correctly determine their treatment assignment over a 2‐month period. We hope that this study design will help inform future trials so that patients' experiences of symptoms are more reliably measured.